Prevalence of Hypertension, Diabetes, and Other Cardiovascular Disease Risk Factors in Two Indigenous Municipalities in Rural Guatemala: A Population-Representative Survey - Eric Steinbrook; David Flood; Joaquin Barnoya; Carlos Mendoza Montano; Ann C. Miller; Peter Rohloff (Ubiquity Press, 2022)
Background: Nearly 50% of Guatemalans are Indigenous Maya, yet few studies have examined the prevalence of modifiable cardiovascular disease (CVD) risk factors in Indigenous Maya populations. Therefore, we sought to estimate the prevalence of modifiable CVD risk factors in two Indigenous Maya areas in Guatemala. Methods: We conducted, between June 2018 and October 2019, a population-representative survey of adults aged 18 years and older in two rural Indigenous Maya municipalities in Guatemala. Our primary outcomes were five modifiable CVD risk factors: diabetes, hypertension, obesity, smoking, and alcohol use. We estimated the crude and age-standardized prevalence of each outcome. We also constructed multivariable logistic regression models to assess prevalence over covariates including age, sex, education level, ethnicity, and poverty. Sampling weights adjusted for nonresponse, and appropriate survey commands were used in all analyses. Results: The crude prevalence of diabetes was 12.5% (95% confidence Interval [CI] 9.6% to 16.1%), hypertension 20.3% (95% CI 17.1% to 23.9%), obesity 23.7% (95% CI 19.4% to 28.6%), smoking 10.7% (95% CI 7.8% to 14.5%), and high alcohol use 0.9% (95% CI 0.5% to 1.6%). Age-standardized prevalence of each outcome was similar to the crude prevalence. The prevalence of multiple CVD risk factors increased between the age groups 18-29 years and 50-59 years before decreasing among older age groups. Men had twenty-fold higher smoking prevalence than women (20.5% vs. 1.2%, respectively) and women had nearly double the age-adjusted prevalence of obesity as men (30.1% vs. 17.0%, respectively). Conclusion: There is a substantial prevalence of modifiable CVD risk factors in rural, Indigenous populations in Guatemala, in particular hypertension, diabetes, obesity (among women), and smoking (among men). These findings can help catalyze policy and clinical investments to improve the prevention, management, and control of CVD risk factors in these historically marginalized communities.